PARTISIPASI PETANI DALAM PROGRAM BIOINDUSTRI BERBASIS INTEGRASI PADI DAN SAPI DI DESA PONCOKRESNO KECAMATAN NEGERI KATON KABUPATEN PESAWARAN - Utami, Yesi Lufi; Hasanuddin, Tubagus; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purposes of this research are to analyze implementation of bioindustrial program, the level of farmer’s participation,and factors associated with participation.Research was conducted in August-September 2017. All 44 farmer members of four farmer groups carying out the Bioindustry program are respondents. Data were analyzed descriptively using Rank Spearman correlation test. Results showed that the program is implemented well and structured. The implementation phase consists of: village potential surveys, formation of farmer groups, and socialization and training activities. The four farmer groups conduct different activities, namely: makinh biogas by Tunas Harapan farmer group, making biourine by Harapan Jaya farmer group, and making compost by Mulia Jaya and Mekar Berseri farmer groups. The products of Bioindustry program are exhibited among farmer groups. The participation rate of farmers in the program is classified as high. Factors related to farmers’ participation in the Bioindustry program are frequency on extension activities, land size, and the number of cattle owned. Key words: bioindustry, implementation, participation